We Rebel: Black Women, Worker Theater, and Critical Unionism in Wartime St. Louis. Issue 1 (14th March 2016) - Ervin, Keona K.
Abstract : Black working-class women developed a powerful and dynamic critical unionism amid the social upheavals generated by wartime mobilizations of the 1940s. The first cohort to more fully integrate the St. Louis garment and apparel industry and its unions articulated a Black labor feminist agenda that made critical interruptions and interventions into industrial labor and liberal racial unionism through resistance and performance. Exposing the racialized and gendered fault lines of shopfloor production, union bureaucracy, racial liberalism, historical memory, and the cultural politics of labor education, Black women unionists opposed the historical narratives of worker theater that drew upon Old South nostalgia and failed to account for their particular economic experiences. By the same token, they enthusiastically participated in performances and cultural programs that reflected their pro-labor sentiment, celebrated their artistry, and strengthened interracial worker solidarity by foregrounding shared political interests. Although integration within the mounting civil rights movement of the 1940s was not the most important agenda item for these working people, they nonetheless made critical contributions to larger civil rights and wartime challenges through their dimensional labor practices.